Off‐Flavour Removal With Advanced Oxidation Process and Hydrogen Peroxide Treatments in Recirculating Aquaculture Systems - Samu Pettersson; Petra C. Lindholm‐Lehto; Jani T. Pulkkinen; Tuula Tuhkanen (Aquaculture, Fish and Fisheries)
ABSTRACT Aquaculture is becoming increasingly important for the world's food production. Recirculating aquaculture system (RAS) has a reduced water requirement and better possibilities for waste handling. Unfortunately, off‐flavours can be formed in RAS and concentrate on fish flesh. Off‐flavour compounds cause earthy, musty or other unwanted flavours to fish flesh that consumers find objectionable. Typically, off‐flavours are removed by depurating the fish in clean water, but it often takes from days to weeks to fully remove these unwanted flavours that causes additional costs to fish producers. Therefore, reliable methods to reduce the need for depuration are needed. In this study, two methods were investigated for the removal of off‐flavours in RAS rearing rainbow trout Oncorhynchus mykiss: an advanced oxidation process (AOP) using a combination of ozone (O3) and hydrogen peroxide (H2O2), and a treatment with H2O2 alone. Two treatments (AOP and H2O2) and a control without oxidants were applied across nine identical experimental RASs for 8 h day−1 over 10 days, and selected off‐flavour compounds in water and fish were analysed. In fish, the concentrations of GSM and MIB were on average 776 and 962 ng kg−1 (AOP) and 688 and 919 ng kg−1 (H2O2) compared to 1071 and 1205 ng kg−1 in the controls. The results showed that intensive oxidant treatments reduced the off‐flavour concentrations in the recirculating water and in fish, which can potentially lead to reduced depuration time and production costs. Further optimization of the treatment is needed to improve off‐flavour removal efficiencies.